2020
DOI: 10.1021/acsomega.0c04822
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Highly Volatile Fragrances in Y Zeolites for Sustained Release: Experimental and Theoretical Studies

Abstract: Volatility is an inherent fragrance attribute and typically implies a reduced perception over time. One possibility to elongate odor perception is utilizing controlled fragrance-delivery systems. Herein, the Y type of faujasite with different extraframework cations (abbreviated as ZY, where Z represents Na + , Ca 2+ , or La 3+ ) was examined as potential carriers for fragrance entrapment and delivery. D-Limonene (Lim) and linalool (Lol) as model fragrances were loaded in the pore space of Y zeolites, yielding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 70 publications
1
15
0
Order By: Relevance
“…In this study, the fumigant persistence of E. largiflorens essential oil was improved by encapsulation in MCM-41 and Zeolite 3A. Although both physical and chemical mechanisms may be considered in loading and releasing essential oils from porous materials, research is often focused on physical means due to the presence of several nanopores in these materials [ 31 , 66 ]. For example, Milićević et al [ 67 ] indicated that zeolite adsorbs the droplets of clove bud essential oil due to its porosity; the insecticidal, antifungal, and antibacterial effects of essential oils were augmented by loading in this porous material.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the fumigant persistence of E. largiflorens essential oil was improved by encapsulation in MCM-41 and Zeolite 3A. Although both physical and chemical mechanisms may be considered in loading and releasing essential oils from porous materials, research is often focused on physical means due to the presence of several nanopores in these materials [ 31 , 66 ]. For example, Milićević et al [ 67 ] indicated that zeolite adsorbs the droplets of clove bud essential oil due to its porosity; the insecticidal, antifungal, and antibacterial effects of essential oils were augmented by loading in this porous material.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there has been growing interest in the application of mesoporous nanoparticles, such as zeolites and MCM-41, ranging from adsorption to active ingredient delivery [ 30 ]. Nanoencapsulation of highly volatile fragrances, such as essential oils and their components, in zeolites and MCM-41 for controlled release and enhancement of their durability is one of the recent promising applications of mesoporous materials [ 31 , 32 ]. For example, the antibacterial activity of film nanocomposite made from zein film and cinnamon essential oil was significantly prolonged by loading the essential oil in MCM-41 for application in long-term packaging [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zeolites not only offer a stable framework, specific ion exchange properties, and adsorption capacities, but their porous nature and inherent pH-sensitive properties also enable the entrapment and selective release of the encapsulated compounds [ 61 , 97 , 99 , 100 , 101 ]. This effect could be beneficial for acid tumor environments, topical applications, or textile applications.…”
Section: Zeolites As Carriers For the Encapsulation Of Essential Oilsmentioning
confidence: 99%
“…They also found that zeolite had lower encapsulation capacity than MOFs (Basolite C300 and Basolite A520). Zeolites with different framework cations (Na + , Ca 2+ , or La 3+ ) were investigated as potential carriers for limonene and linalool entrapment and delivery (Li et al., 2020). The retention of volatiles in the matrices increases in the order Na > Ca > La for either limonene or linalool.…”
Section: Triggered and Controlled Release Of Active Gases/volatiles T...mentioning
confidence: 99%